Pengaruh Mutu Pelayanan terhadap Tingkat Kepuasan Pasien Rawat Inap di Puskesmas Lapai Kabupaten Kolaka Utara - Lisna; Muhammad Syafar; Muhammad Rifai (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
Public services in the health sector can be carried out in hospitals and health centers throughout Indonesia. Community Health Center is a service facility that organizes public health efforts and first-level individual health efforts, by prioritizing promotive and preventive efforts, to achieve the highest public health degree in its working area. The purpose of the study was to influence service quality on the level of satisfaction of inpatients at the Lasusua Public Health Center, North Kolaka Regency in 2021. The type of research used was an analytical survey research with a "cross-sectional" design, where all observed variables were measured simultaneously. when the research took place. The results show that physical evidence affects the level of patient satisfaction with a value of value (0.000) Reliability affects the level of patient satisfaction with a value of value (0.000) Responsiveness affects the level of hospitalization satisfaction with a value of value (0.001), Guarantee affects the level of satisfaction patient satisfaction with a value of value (0.013) Empathy affects the level of patient satisfaction with a value of value (0.000) and the most dominant variable on the level of satisfaction of inpatients at the Lapai Health Center, North Kolaka Regency is physical evidence with an Exp (B) or OR value of 107,823. Suggestions in research are to become information and input for the health office to improve the quality of health services at the puskesmas, can be input for the puskesmas to always continue to improve the quality of services provided to patients in order to achieve patient satisfaction and become reference material and information for research. The next is related to the quality of service to patient satisfaction